Effect of nickel nanofillers on the dielectric and magnetic properties of composites based on rubber in the X-band - Jamal, E. Muhammad Abdul; Mohanan, P.; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Applied Physics A-Materials Science & Processing, 2009)
Nickel-rubber nanocomposites were synthesized by incorporating ferromagnetic nickel nanoparticles in a natural rubber as well as neoprene rubber matrix. Complex dielectric permittivity and magnetic permeability of these composites were evaluated in the X-band microwave frequencies at room temperature using cavity perturbation technique. The dielectric loss in natural rubber is smaller compared to neoprene rubber. A steady increase in the dielectric permittivity is observed with increase in the content of nickel in both the composites. The magnetic permeability exhibits a steady decrease with increase in frequency and magnetic loss shows a relaxation at 8 GHz. The suitability of these composites as microwave absorbers is modeled based on the reflection loss which is dependant on the real and imaginary components of the complex dielectric permittivity and magnetic permeability.